High Depolarization Ratios of Naturally Occurring Cirrus Clouds Near Air Traffic Regions Over Europe - Benedikt Urbanek; Silke Groß; Martin Wirth; Christian Rolf; Martina Krämer; Christiane Voigt (Geophysical Research Letters)
Abstract Cirrus clouds have a large influence on the Earth's climate and anthropogenic activities such as aviation can alter their properties. Besides the formation of contrails, indirect effects on naturally occurring cirrus like increased heterogeneous freezing due to exhaust soot particles are discussed in the literature. However, hardly any observational study exists. In this work we present cirrus optical properties measured by an airborne lidar over Europe during the Midlatitude Cirrus experiment (ML‐CIRRUS). One half of the cloud cases showed elevated depolarization ratios with a mode difference of 10 percentage points indicating differences in the clouds microphysical properties. Their origin can be traced back to highly frequented air traffic regions, and they show lower in‐cloud ice supersaturations. Our analysis reveals no influence of embedded contrails and temperature. These results could be explained by an indirect aerosol effect where heterogeneous freezing is caused by aviation exhaust particles.